2019
DOI: 10.1523/eneuro.0495-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Neuron-Optimized CRISPR/dCas9 Activation System for Robust and Specific Gene Regulation

Abstract: CRISPR-based technology has provided new avenues to interrogate gene function, but difficulties in transgene expression in post-mitotic neurons has delayed incorporation of these tools in the central nervous system (CNS). Here, we demonstrate a highly efficient, neuron-optimized dual lentiviral CRISPR-based transcriptional activation (CRISPRa) system capable of robust, modular, and tunable gene induction and multiplexed gene regulation across several primary rodent neuron culture systems. CRISPRa targeting uni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 65 publications
2
112
0
Order By: Relevance
“…4i-j, Supplemental Figure 9), a region critical for the development and maintenance of sensitization (48,49). We previously validated robust and neuron-selective expression of this CRISPRa system in vivo within 2 weeks of viral delivery into the NAc, and demonstrated that this tool results in elevated protein levels of target genes (35). Eighteen days after viral infusion, rats underwent locomotor sensitization testing in a novel environment using a dose of cocaine (10mg/kg) that does not reliably produce robust sensitization (50,51).…”
Section: Controlmentioning
confidence: 94%
See 3 more Smart Citations
“…4i-j, Supplemental Figure 9), a region critical for the development and maintenance of sensitization (48,49). We previously validated robust and neuron-selective expression of this CRISPRa system in vivo within 2 weeks of viral delivery into the NAc, and demonstrated that this tool results in elevated protein levels of target genes (35). Eighteen days after viral infusion, rats underwent locomotor sensitization testing in a novel environment using a dose of cocaine (10mg/kg) that does not reliably produce robust sensitization (50,51).…”
Section: Controlmentioning
confidence: 94%
“…However, drugs of abuse target many distinct receptor classes in a variety of neuronal and non-neuronal cell types (20,21), and these complex drug actions make identification of DA-induced gene expression programs difficult using in vivo models. Therefore, we took advantage of a well-studied and controllable rat primary striatal neuron culture system (35,36) to enable comprehensive and specific identification of DA-dependent gene expression programs in MSNs. Using this system, we first identified a core signature of the transcriptional response to DA receptor activation by performing deep RNA-seq on bulk striatal neuronal cultures treated with 1µM DA for 1hr, a treatment that closely models concentrations and temporal duration of DA increases found in vivo after acute cocaine exposure (2,3,6).…”
Section: Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Innovations and adaptations of CRISPR/Cas9 technologies comprise the inclusion of LoxP/Cre sites on recombination templates (to allow removal of selection markers from established knock-in/out lines) and the SapTrap system derived from GoldenGate cloning, which provides a simple way to make a variety of knock-in/out repair constructs (Au et al, 2019;Schwartz & Jorgensen, 2016). CRISPR interference and CRISPR activation (CRISPRi and CRISPRa, respectively) have also been successful in C. elegans (Long et al, 2015;Savell et al, 2019).…”
Section: Of 35mentioning
confidence: 99%